TINGKAT FANATISME PENGGEMAR MUSIK POP KOREA (K-POPERS) TERHADAP BUDAYA K-POP PADA KOMUNITAS EXO-L PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The most popular South Korea pop culture nowdays is Korean Pop Music (K-Pop). Korean pop music fans (k-popers) behaviors that is sometimes overreact in supporting their idols make them synonymous with fanatical traits, giving rise to negative views from ordinary people who see them. One of the k-popers community in Pekanbaru is EXO-L Pekanbaru. This community is one of the biggest k-popers community in Pekanbaru that have most followers in social media and the most active community in holding k-pop activities. The aims of this research were to know the level of korean pop music lovers (K-Popers) fanaticism to k-pop culture of EXO-L Community in Pekanbaru and also to know the factors that influencing fanaticism to k-pop culture of EXO-L Community in Pekanbaru. The method used in this research is quantitative descriptive method. The population and sample in this research were all the active members of EXO-L Community Pekanbaru totaling 98 respondents. This research data was obtained by observation, questionnaire, and documentation. Data analysis was carried out by data coding, then tabulated and described by descriptive quantitative analysis. The result in this research is the level of korean pop music lovers (K-Popers) fanaticism to k-pop culture of EXO-L Community in Pekanbaru are in the high category (48.0%),  moderate category (45.9%), and low category (6.1%) with the mean value () of all respondents is 70,22. Overall, it can be concluded that the level of fanaticism is in the moderate category. The factors that influencing the fanaticism are emotional factor, idol’s self image factor, friendship environment factor, cultural factor, and social media factor. Based on these five factors, the biggest influence is emotional factor with the total score is 432.     Keywords: Fanaticism, K-Popers, K-Pop